Income inequality and saving - Francisco Alvarez-Cuadrado; Mayssun el Attar (Institute for the Study of Labor (IZA), 2012)
Over the last three decades, average income for the bottom half of the US distribution increased by 8% while their average saving rate decreased by eight percentage points. Over the same period the US experienced a substantial increase in inequality and a continuous decrease in the aggregate saving rate. We propose an explanation based on interpersonal comparisons consistent with these trends. When households care about their consumption relative to others, individual saving rates decrease with reference income while aggregate saving decreases with income inequality. We provide evidence from the PSID and a panel of OECD countries consistent with these predictions.
Keywords: D91; E21; C23; 330; relative consumption; income inequality; saving; Einkommensverteilung; Einkommenshypothese; Konsuminterdependenz; Sparen; Schätzung; USA; OECD-Staaten